Moderate and Severe Postendoscopic Retrograde Cholangiopancreatography Pancreatitis Despite Prophylactic Pancreatic Stent Placement: The Effect of Early Prophylactic Pancreatic Stent Dislodgement - Dana C Moffatt; Pradermchai Kongkam; Haritha Avula; Stuart Sherman; Evan L Fogel; Glen A Lehman (Canadian Journal of Gastroenterology)
BACKGROUND: Placement of prophylactic pancreatic stents (PPS) is a method proven to reduce the rate and severity of postendoscopic retrograde cholangiopancreatography (ERCP) pancreatitis (PEP) in high-risk patients; however, PPS do not eliminate the risk completely. Early PPS dislodgement may occur prematurely and contribute to more frequent or severe PEP.